Stress and coping among psychology students - Cassaretto, Mónica (2003)
The relations among stress, problems and coping styles among 123 psychology  students. in aprivate university in Lima, were analyzed. Four instruments were used: a) Demographic Sheet (Cassaretto, Oblitas & Valdez, 2000), b) Stress Response Questionnaire (Valdez, 1999), e) Co ping Inventory (Carver, Scheier & Weintraub, 1989), d) Problem Questionnaire (Seiffge Krenke, 1995). Variables as age, sex, job, stress responses, problems and coping styles were considered. The results showed that older people have higher stress levels, the problems related with future and self being the most stressful; finally, problem and emotion coping styles are related to lower levels of stress.